Circadian disruption by light and its effect on the immune function of the Atlantic salmon (Salmo salar) - Solberg, Therese (UiT Norges arktiske universitet, 2022)
The Atlantic salmon (Salmo salar) is an anadromous salmonid that begins its life cycle in freshwater streams then, develops, in a process known as smoltification, into a marine-adapted fish prior to its migration to the sea. Smoltification is a photoperiod regulated process which involves extensive change in the salmons’ physiology. In recent years smoltification procedures in aquaculture has been linked to a downregulation of the immune system, but the underlying cause remains unknown. In mammals, the circadian clock drives 24h cycles in immune system capacity and recent work links circadian clock disruption, including through exposure to constant light, to an impaired immune response. These data are particularly relevant in an aquaculture context where constant light is used routinely in smoltification protocols. Here, we hypothesise that the downregulation of the immune system in aquaculture smoltification protocols is a consequence of circadian clock disruption caused by exposure to constant light. To investigate our hypothesis, we performed two different smoltification protocols, one under long photoperiod 18 h L: 6 h D (LD), providing both photoperiodic stimulation and circadian entrainment, and a second under constant light (LL), which receives photoperiodic stimulation but in a potentially disruptive circadian environment. We next characterised the smolt phenotypes of each of these groups then compared their immune competence by SAV3 immune challenge. Both LD and LL protocols induced classical smolt characteristics. In contrast to earlier work, we did not observe a decrease in the expression of a panel of immune genes, and there were not a difference between the LD and LL groups, suggesting that the immune marker genes Cd3e, Csf1r and IL10rb are not robustly associated with smoltification. Following SAV3 challenge, qPCR analysis of immune response markers in head kidney and heart, revealed no difference in viral response between LD and LL groups. These findings were supported by an in vitro leukocyte ...